Anesthesia for a Patient with an Orbital Mass Complicated by Recent Coronary Stenting and Pulmonary Artery Hypertension Due to Langerhans Cell Histiocytosis: the Role of Awake Pulmonary Artery Catheterization. Issue 1 (2018) - Sato, Keita; Rotenberg, Brian; Murkin, John M
No abstract available